Status gizi dan hubungannya dengan kejadian diare pada anak diare akut di ruang rawat inap RSUP Dr. Sardjito Yogyakarta - Astya Palupi; Hamam Hadi; Sri Suparyati Soenarto (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2009)
Background: in Indonesia diarrhea is still a major cause of morbidity and mortality among children especially those under five years of age. The Household Health Survey 2000 and 2003 shows an increase of diarrhea morbidity rate from 300 to 374 per 1,000 people. At the inpatient ward of Dr. Sardjito Hospital in 2005, diarrhea was found as the major cause of patients being hospitalized. One of the causes of high diarrhea morbidity rate is poor nutritional status. In 2002, the prevalence of undernourished children in Indonesia was 27.3% and in the Province of Yogyakarta Special Territory was 11.39%. Ultimately, nutritional status and diarrhea are related to each other, which lead to very famous